Archive Management Procedures at Pt Jasa Raharja Representative Tk 1 Medan - Wulandari, Sri Eka; Sari, Wulan Aprita (Cattleya Darmaya Fortuna, 2023)
In an organization, archives play a role as a provider of information and for decision making. Archive management is one of the important activities carried out at PT Jasa Raharja TK 1 Medan Representative, this archive management aims to make archive storage more systematic and structured. Archive management carried out at PT Jasa Raharja has not used the correct management procedure, marked by the difficulty in retrieving claim documents that have been used because the documents are not neatly arranged. Therefore, it is necessary to have management such as archive maintenance which can help make it easier for employees to find archives again. The analytical method used in this research is a qualitative descriptive method and the data taken is primary data which can be directly through observation and interviews. The results of this study indicate that archives have a very important role at PT Jasa Raharja Representative TK 1 Medan, as evidenced by the difficulty in retrieving archives which hinders employee performance. Therefore, it is necessary for archivists to check and rearrange the archive shelves according to the archive classification.